Knowledge, attitudes, and practices toward tuberculosis among Jordanian university students - Abu-Humaidan, Anas H. A.; Tarazi, Alaa; Hamadneh, Yazan; Al-leimon, Ahmad; Al-leimon, Obada; Aljahalin, Mohammad; Ahmad, Fatima; Awajan, Dima; Alaridah, Nader (Frontiers in Public Health, 2022)
Background Tuberculosis (TB) is one of the leading causes of death from infectious diseases worldwide with numerous undiagnosed and untreated cases, emphasizing the need for TB awareness to minimize transmission and initiate early treatment. Data regarding the knowledge, attitudes, and practices (KAP) toward TB among Jordanians is lacking but requires attention given the massive migration spells to Jordan from neighboring countries in the past decade. Methods A descriptive cross-sectional study was conducted from May to June 2022. An online questionnaire was developed following World Health Organization (WHO) recommendations for TB KAP surveys and was distributed to Jordanian university students. The questionnaire documented sociodemographic data and measured participants' KAP toward TB. Descriptive and analytic statistics were used to report KAP levels and highlight relevant sociodemographic factors associated with better KAP. Results 602 participants completed the survey; most were females (60.8%), in their first 3 years of school (84.4%), and from a healthcare field of study (57.0%). The knowledge section median score was 27 out of 51. Knowledge gaps in TB treatment, and to a lesser extent, TB transmission routes were identified. The attitudes section median score was 6 out of 9, attitudes were generally positive toward TB patients with no indication of a social stigma. The practice section median score was 6 out of 8, most participants would take the correct measures if they suspected being infected, yet around 41.0% were not confident that masks are important in preventing airborne diseases. Students in healthcare specialties had significantly better KAP scores and identifying as a smoker was associated with a lower practice score. Conclusion Although university students displayed satisfactory KAP scores, the focus should be aimed at informing students from non-healthcare fields on TB transmission routes, treatment options, and the role of masks in preventing disease transmission.